2020
DOI: 10.2139/ssrn.3600088
|View full text |Cite
|
Sign up to set email alerts
|

The Persuasive Effect of Fox News: Non-Compliance with Social Distancing During the Covid-19 Pandemic

Abstract: We test for and measure the effects of cable news in the US on regional differences in compliance with recommendations by health experts to practice social distancing during the early stages of the COVID-19 pandemic. We use a quasi-experimental design to estimate the causal effect of Fox News viewership on stay-at-home behavior by using only the incremental local viewership due to the quasi-random assignment of channel positions in a local cable line-up. We find that a 10% increase in Fox News cable viewership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 86 publications
6
67
1
Order By: Relevance
“…Approaches might include fostering trust in science, identifying ways for citizens to participate in research, and improving science communication (Boele-Woelki et al, 2018), community engagement (Pham, 2016; also see Wynne, 2006, for critical analysis), and the adoption of open-science practices (Funk and Kennedy, 2019;Grand et al, 2012). This will be particularly important in situations where attacks on scientific expertise by segments of the media and political actors are commonplace and contribute to science denial and opposition to evidence-based policy (Bursztyn et al, 2020;Gauchat, 2012;Leiserowitz et al, 2013;Lewandowsky et al, 2016;Lewandowsky and Cook, 2020;Simonov et al, 2020). While a crisis presents an opportunity to build public trust by engaging in honest and transparent communication, as detailed in this paper, trust can also be rapidly lost if the expert is perceived as a political pawn or their credibility is attacked.…”
Section: Pandemic Communications: Foundations and Recommendationsmentioning
confidence: 93%
“…Approaches might include fostering trust in science, identifying ways for citizens to participate in research, and improving science communication (Boele-Woelki et al, 2018), community engagement (Pham, 2016; also see Wynne, 2006, for critical analysis), and the adoption of open-science practices (Funk and Kennedy, 2019;Grand et al, 2012). This will be particularly important in situations where attacks on scientific expertise by segments of the media and political actors are commonplace and contribute to science denial and opposition to evidence-based policy (Bursztyn et al, 2020;Gauchat, 2012;Leiserowitz et al, 2013;Lewandowsky et al, 2016;Lewandowsky and Cook, 2020;Simonov et al, 2020). While a crisis presents an opportunity to build public trust by engaging in honest and transparent communication, as detailed in this paper, trust can also be rapidly lost if the expert is perceived as a political pawn or their credibility is attacked.…”
Section: Pandemic Communications: Foundations and Recommendationsmentioning
confidence: 93%
“…Perceived severity was also indicated by the number of media sources of information people used to learn about COVID-19 in the past 7 days. While different sources of media and public health agents may deliver different messages about severity and recommended responses to the pandemic (Ash, Galletta, Hangartner, Margalit, & Pinna, 2020 ; Simonov, Sacher, Dubé, & Biswas, 2020 ), we assume that the more sources they accessed, the more severe they perceived the pandemic to be. The 10 sources we used include ABC news, CBS news, CNN, Fox news, MSNBC news, NBC news, national newspapers such as the New York Times, Washington Post, and USA Today, local newspapers, public television and radio, and local TV news.…”
Section: Methodsmentioning
confidence: 99%
“…They suggested that social distancing would play a critical role in controlling a potential pandemic. Currently, the world is experiencing a pandemic called COVID-19, and a call for social distancing is heard around the world to reduce interactions between people to prevent the transmission (Knowles et al, 2020;Patil & Patil, 2020;Simonov et al, 2020;Tucker & Yu, 2020). This social distancing includes the closure of schools or office buildings and suspension of shopping malls, travel restrictions, and gatherings (Wilder-Smith & Freedman, 2020).…”
Section: Social Distancing and Brandingmentioning
confidence: 99%